Analisis Peran Guru Kelas dan GPK dalam Menangani Siswa ABK (Anak Berkebutuhan Khusus) SDN Cimone 7 Kota Tangerang - Septy Nurfadhillah; Cahaya Hasanah; Deva Elfrisca; Farida Farida; Nopika Ayu Lestari; Siti Fadhilatul Barokah; Zahra Hanifah (ALSYS, 2022)
This study aims to review how the role of teachers and GPK (special assistant teachers) when dealing with ABK students (Children with special needs) at SDN Cimone 7 Tangerang City. Using a descriptive qualitative approach, 1 teacher in charge of inclusion and 1 GPK (special assistant teacher) were used as research subjects. Data collection techniques through direct observation, interviews, and documentation. The data results are analyzed using data condensation steps, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). The results showed that the teacher had carried out adaptive learning for students with special needs (children with special needs) by adjusting the conditions of each of these students. These adjustments relate to methods, strategies, materials and learning media.